Optimizing antifungal therapy: a systematic review of pharmacist interventions, stewardship approaches, and outcomes - Zunaira Akbar; Zunaira Akbar; Muhammad Aamir; Zikria Saleem (Frontiers in Medicine)
IntroductionSpecific evidence regarding the pharmacist’s role in antifungal stewardship (AFS) is emerging. This review aims to identify pharmacist-driven AFS interventions to optimize antifungal therapy.MethodsA systematic review was conducted using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data (2018–2023) were collected through Google Scholar and PubMed. The collected data were presented descriptively due to variations in interventions and outcome metrics. Conclusions were derived through a qualitative synthesis of the identified findings.ResultsA total of 232 articles were retrieved, and after applying inclusion and exclusion criteria, 27 were included in the review. Among the eight studies evaluating the impact of pharmacist interventions on antifungal consumption, 6 studies reported a significant decline in defined daily dose (DDD)/1,000 patient days and days of therapy (DOT)/1,000 patient days, one reported a non-significant decrease, and one reported an increase in the utilization of echinocandins. Educational intervention was the most commonly used stewardship approach. Nineteen studies reported data on various clinical outcomes. Mortality and length of hospital stay remain non-significant, but the occurrence of ADR decreased significantly, and the quality of antifungal use improved significantly.ConclusionPharmacist-led AFS has the potential to enhance the effectiveness of antifungal treatments by improving their overall quality, reduction in consumption, and adverse events. The healthcare system should encourage multidisciplinary collaboration where pharmacists play a central role in decision-making processes regarding antifungal use.